ARTIFICIAL INTELLIGENCE ADDICTION TERHADAP KEMANDIRIAN BELAJAR PADA MAHASISWA BAHASA DAN SASTRA ARAB - Ulil Albab; Isnaini Rahmawati; Riska Ananda; Muhammad Fajri Adha; Surya Rizki Putra; Reza Pahlepi (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The purpose of this research is to examine the relationship between Artificial Intelligence technology and students' learning independence in completing academic tasks, as well as to assess the level of AI addiction and the level of learning independence among Arabic Language and Literature students. This study employs a quantitative research approach with an ex-post facto design to investigate the relationship between Artificial Intelligence addiction and learning independence. The results of this research indicate that the level of Artificial Intelligence addiction is lower compared to students who are not addicted in completing the academic tasks of Arabic Language and Literature students. The level of learning independence is higher compared to students who are not independent in completing the academic tasks of Arabic Language and Literature students. Furthermore, there is a significant relationship between Artificial Intelligence addiction and learning independence among Arabic Language and Literature students.